Я познаю мир. Амфибии: детская энциклопедия / [автор-составитель Б. Ф. Сергеев ; художники: А. В. Куташов Л. Л. , Сильянова ; редактор Е. М. Иванова] - Сергеев Борис Федорович (АСТ, 1998)
Экземпляры: ф.12 (1999) / Инвентарный номер: 40850 / Цена: / Сис.шифр: 28.69 / Авт.знак: Я 11 / ГРНТИ: 34 / ББК: 28.693.33я2